Public libraries: the often forgotten agent of national development (2007)
This paper is about the role public libraries play in national development. The paper traced the history of early libraries and the origin of public libraries in Nigeria. Various services provided by public libraries were also highlighted. Public library power, its implications for all-round development and reasons why public libraries are often forgotten in national development is the main thrust of the paper. However, the paper concluded by lamenting that, though library power is real, but sadly today it is largely ignored, virtually unexplored, and almost forgotten. The paper made recommendations on how the inherent power of the potentials of public libraries can be fully harnessed for national development.